Character Scale for Assessing Discipline and Learning Responsibilities Character in Elementary School - Maria Sumunaringtyas; Tiara Faniska D; Edi Istiyono; Farida Agus Setiawati (Jurnal Ilmiah Sekolah Dasar, 2024)
Assessment is an important process in the learning series that needs to be carried out as well as possible using clear and high-quality instruments. Assessment of the character of discipline and responsibility in one elementary school was only carried out based on teacher observations. This can indirectly make the assessment subjective from the teacher's perspective only. This research aims to produce a collection of instruments for assessing the character of discipline and responsibility in the form of a quality self-scale. This type of research is development research carried out using the development instrument stage. The number of items developed in this research was 20 statements. After being analyzed using CFA, a total of 14 statements were obtained which can be used to measure discipline and responsibility character. The data collection technique used in this research used a validation sheet and a self-scale with a 5-category Likert. Validity is calculated using the Aikens formula and produces a high score. Meanwhile, the estimated reliability of this instrument was calculated using Composite Reliability, producing a number >0.7, which means the instrument has high reliability. Proof of validity and reliability has been fulfilled so that the instrument can be used in assessing discipline and responsibility character. Through a valid and reliable instrument, more accurate measurement data will be obtained, and objectivity in character assessment will be guaranteed. The research implications are in the self-scale which can be used as a balance in latent character assessment.